Cross-Cultural Patterns of Student Victimization in Israel and Chile - Bilbao-Ramirez, M (Springer New York LLC, 2018)
School violence is a global concern that calls for international research using cross context methods. Although there are several international surveys that compare school violence across countries, they do not clearly address issues of similarities and differences in relative prevalence of different types of victimization and their relations with age, sex, and cultural group. We explored these questions among Israeli-Arab (n = 13,606), Israeli-Jewish (n = 10,637), and Chilean students in poor schools in a large Chilean city (n = 4557), using the same self-report questionnaire that measures verbal-social victimization, victimization by threats, physical victimization, and sexual harassment. As hypothesized, we found similarities in the patterns of relative prevalence of victimization types, as well as study group, sex, and age main effects and interactions. These effects were evident even when the lowest third SES group in Israel was compared with the Chilean students. These findings suggest group differences in prevalence of student victimization, and at the same time cultural invariance in relative prevalence of victimization types and their relations with sex and age. We discuss the need for more international comparative research in this field that takes into account cultural values and the structure and organizations of schools within the different educational systems. © 2017, Springer Science+Business Media, LLC.